[South Australia] 1:50 000 topographic series, cadastral overprint : [Map type D3]. 6130-IV,. Kielpa - South Australia. Department of Lands (Adelaide (S. Aust.) : Department of Lands, 1978)
Topographic map with relief shown by contours and spot heights with cadastral information overprinted in purple.
Includes indexes to hundreds and adjoining sheets.
Other title information taken from panel title.
Also available online
Keywords: Real property -- South Australia -- Kielpa -- Maps; Kielpa (S.A.) -- Maps